2019
DOI: 10.1538/expanim.18-0102
|View full text |Cite
|
Sign up to set email alerts
|

The acute pulmonary toxicity in mice induced by <i>Staphylococcus aureus</i>, particulate matter, and their combination

Abstract: Inhalation of pathogenic bacteria transported by particulate matter (PM) presents an important potential threat to human health. Therefore, the pulmonary toxicity in mice caused by Staphylococcus aureus ( S. aureus ) and PM as individual matter and mixtures was studied. PM and S. aureus were instilled intratracheally into Kunming mice at doses of 0.2 mg/mouse and 5.08 × 10 6 CFU /mouse, respectively, as individual matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
4
13
0
Order By: Relevance
“…Previous studies also suggested that some external stimulations, such as particular matter and carbon nanotubes, could increase the various types of inflammatory cells in BALF 25,26 . In our study, the number of inflammatory cells in BALF were also increased in CBs treated mice and Y‐27632 could appear to suppress the increase of inflammatory cells caused by CBs.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies also suggested that some external stimulations, such as particular matter and carbon nanotubes, could increase the various types of inflammatory cells in BALF 25,26 . In our study, the number of inflammatory cells in BALF were also increased in CBs treated mice and Y‐27632 could appear to suppress the increase of inflammatory cells caused by CBs.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, we analyzed the regulatory function of Prx I on both lethal shock reaction and host immune response to S. aureus infection in mice. Several studies have previously shown that S. aureus promotes a host immune response from minor skin infections to severe systemic inflammations, including septic lethal shock (17,18). TLR2 is known as a key molecule to contribute to host immune response against S. aureus infections (19,20), and deletion of TLR2 increases the mortality of mice during S. aureus infection (15,(21)(22)(23) combined with impaired cytokines production and severe inflammatory burden.…”
Section: Discussionmentioning
confidence: 99%
“…Te initiation of an infammatory response is marked by an increase in infammatory mediators and proinfammatory cytokines [11]. Reactive oxygen species (ROS), catalase (CAT), heme oxygenase-1 (HO-1), superoxide dismutase (SOD), and glutathione peroxidase (GPX) [12] are factors infuencing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%